2022
DOI: 10.3389/fpubh.2021.751940
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the COVID-19 Epidemic With Multi-Population and Control Strategies in the United States

Abstract: As of January 19, 2021, the cumulative number of people infected with coronavirus disease-2019 (COVID-19) in the United States has reached 24,433,486, and the number is still rising. The outbreak of the COVID-19 epidemic has not only affected the development of the global economy but also seriously threatened the lives and health of human beings around the world. According to the transmission characteristics of COVID-19 in the population, this study established a theoretical differential equation mathematical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Many previous studies have indicated that the asymptomatic group and the undetected group play an important role in the transmission of the COVID-19 epidemic [ 37 , 38 ]. For simplicity, these two groups are not included in our model, but satisfactory adjustment performance can still be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have indicated that the asymptomatic group and the undetected group play an important role in the transmission of the COVID-19 epidemic [ 37 , 38 ]. For simplicity, these two groups are not included in our model, but satisfactory adjustment performance can still be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…A mathematical model of the COVID-19 epidemic with multiple populations and control strategies was put forth by Sun [15]. It included groups for those who were susceptible (S), asymptomatic and undiagnosed (A), symptomatic and diagnosed (AD), symptomatic and infected (I), recovered (R), and dead (D):…”
Section: Constant Term Of the Characteristic Polynomial Methodsmentioning
confidence: 99%
“…We can substitute C * I stated in (25) in (24) and calculated as N * 2 λ * C = σ 2 C * I and gives as…”
Section: The Subdynamical System Dfe Stabilitymentioning
confidence: 99%
“…On March 11, 2020, WHO declared it as one of the major and dangerous worldwide pandemic diseases [13,20,21]. Respiratory air droplets and touching materials contaminated with the virus are the transmission mechanisms [22][23][24][25]. It has been a great health and economic burden for many nations throughout the world [16,22,26].…”
Section: Introductionmentioning
confidence: 99%